The Role of a Godly Mother in Forming Children's Character: Children's Rights in Choosing Their Environment Family - Risana, Fifi; Pratama, Angga; Sampurna, Azet; Erlina, Erlina; Hijriyah, Umi (PT. Hafasy Dwi Nawasena, 2024)
The purpose of this research is to understand the formation of children's personalities, children's rights from an Islamic perspective, and the influence of family dynamics on children's development. This study also analyzes the role of sholehah mothers in supporting the growth of children's character. The analysis carried out is descriptive and interpretive, to dig into the collected data in depth. The data were analyzed using descriptive statistics to find out general trends, while interpretive statistics were used to understand the significance and implications of the findings. Data is collected through various literature sources relevant to the research topic. The results of this study show that a pious mother has a very important role in supporting and motivating her children to reach their best potential. Mrs. Sholehah provides support in various ways, such as giving praise and appreciation for the achievements achieved by the child, providing encouragement and motivation when the child faces challenges, and helping the child achieve his goals. This study confirms that support and motivation from parents, especially mothers, are crucial for children's physical, mental, and emotional development. With sincere attention, children can grow and develop well, become positive individuals and have noble character